Controllable linear-circular polarization conversion of radial variant vector beams in a strongly nonlocal nonlinear medium. (28th May 2019) - Zhang, Xiaoyu; Chew, Khian-Hooi; Liu, Caixia; Wang, Zhongxing; Chen, Rui-Pin
Abstract: The dynamical properties of radial-variant vector beams in strongly nonlocal nonlinear (SNN) media are theoretically demonstrated. The analytical expressions for the variation of root-mean-square (RMS) beam width and the critical powers P cr that keep the RMS beam widths invariant during propagation are derived using the moments method. When the initial power Pin does not equal the critical power P cr, the RMS beam widths evolve periodically. The coherent superposition of different polarization components with different evolution trajectories during propagation in an SNN medium leads to the linear-circular polarization conversion. The linear-circular polarization conversion occurs, especially in the beam center, and the propagation distances between the peak intensities of the converted polarizations can be manipulated by the initial distribution of polarization states and the initial powers. The conversion efficiency and the converted polarization purity during propagation are also analyzed.